Implementasi Model Pembelajaran Project Based Learning Dalam Pembelajaran Menulis Teks Proposal Pada Siswa Kelas XI SMA Negeri 8 Yogyakarta (International Forum of Researchers and Lecturers, 2024)
This research aims to describe the implementation of the learning model project based learning in learning to write proposal texts for class XI students at SMA Negeri 8 Yogyakarta. This research is included in qualitative descriptive research. The subjects in this research were Indonesian language teachers and class XI students of SMA Negeri 8 Yogyakarta, even semester of the 2022/2023 academic year. The objects in this research are learning tools prepared by the teacher and proposal texts produced by class XI students at SMA Negeri 8 Yogyakarta. Data collection in this research was carried out by documentation and observation. The document in this research is the Learning Implementation Plan or Teaching Module. Furthermore, the observations in this research are participatory observations. Based on the analysis of planning, implementation and evaluation of learning, it was concluded that the project based learning model has been able to become a learning model that guides students' independence in learning Indonesian on the topic of activity proposal texts. With this independence, learning will be student-centered, so that the implementation of learning that focuses on new paradigm learning can be achieved optimally.